Relationship of Leukocyte Numbers and Triglyceride Levels in Type 2 Diabetes Mellitus Patients - Nurhilaliyah (Hayyan Journal, 2024)
Diabetes mellitus is a metabolic disorder characterized by hyperglycemia due to abnormalities in insulin secretion, insulin action or both and is included in the group of non-communicable diseases. In patients with type 2 diabetes mellitus, progressive hyperglycemia occurs resulting in insulin deficiency, where insulin deficiency can damage lipoprotein lipase activity and result in lower HDL levels and higher triglyceride levels. High triglyceride levels in type 2 diabetes mellitus patients result in increased macrophage infiltration into adipose tissue which causes an increase in the number of leukocytes. The aim of this research is to determine the relationship between the number of leukocytes and triglyceride levels in people with type 2 diabetes mellitus. This type of research is a quantitative descriptive laboratory observational approach. The number of samples in this research was 35 samples obtained through techniquespurposive sampling. Based on the results of the Pearson correlation static test analysis to determine the relationship between the number of leukocytes and triglyceride levels in type 2 diabetes mellitus sufferers, the sig value was 0.035, while for thePersonal Correlation namely 0.358 so it was concluded that there was a relationship indicating that there was sufficient correlation between the number of leukocytes and triglyceride levels